2014
DOI: 10.1097/hco.0000000000000034
|View full text |Cite
|
Sign up to set email alerts
|

Anthracycline-related cardiotoxicity in childhood cancer survivors

Abstract: Despite major advances in cancer treatment, anthracycline-related cardiotoxicity remains a major cause of morbidity and mortality in survivors of childhood cancer. Promising areas of research include: use of biomarkers for early recognition of cardiac injury in children receiving chemotherapy, development and application of cardioprotective agents for prevention of cardiotoxicity, and advancements in therapies for cardiac dysfunction in children after anthracycline treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 86 publications
1
48
0
Order By: Relevance
“…DOX is a widely used and successful anti-tumor drug; however, its clinical use is limited due to its severe cumulative dose-associated cardiotoxicity (2). Numerous studies have demonstrated that the primary molecular mechanism involved in DOX-induced cardiotoxicity is free radical-induced oxidative stress, and cardiomyocyte death by apoptosis and necrosis (5,22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DOX is a widely used and successful anti-tumor drug; however, its clinical use is limited due to its severe cumulative dose-associated cardiotoxicity (2). Numerous studies have demonstrated that the primary molecular mechanism involved in DOX-induced cardiotoxicity is free radical-induced oxidative stress, and cardiomyocyte death by apoptosis and necrosis (5,22).…”
Section: Discussionmentioning
confidence: 99%
“…However, the clinical use of this valuable anticancer drug is limited by severe toxic side effects on the heart, which may result in heart failure (2). Numerous studies have implicated reactive oxygen species generation in the cardiotoxicity of DOX, which ultimately results in cardiomyocyte apoptosis (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Pathologically, doxorubicin-induced cardiomyopathy was associated with heightened oxidative stress status, apoptosis of cardiac cells, inflammatory response, myocardial fibrosis, metabolism abnormality, DNA damage and mitochondrial damage [37]. Several agents including anti-oxidants, angiotensin-converting enzyme inhibitors (ACEI), angiotensin receptor antagonists (ARB) and dexrazoxan have been employed for the attenuation of doxorubicin-induced cardiomyopathic damage [8, 9]. Unfortunately, all of these agents have not yet gained effective enough evidence to justify a routine use.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic DCM leads to cardiac dysfunction and eventually congestive heart failure, resulting in the need for heart transplant or even causing death [7]. Chronic DCM occurs in about 10-20% of cancer survivors often 10-15 years following treatment [3,8,9]. As the likelihood of DCM cannot be assessed a priori for an individual patient, the usual dosage of DOX is usually restricted to 60-75 mg/m² every 3 weeks, hence limiting its efficacy [10].…”
Section: Introductionmentioning
confidence: 99%